Keputusan Tata Usaha Negara Fiktif Berdasarkan Hukum Positif Di Indonesia - Farid Ramdani (University of Merdeka Malang, 2018)
This study aims to examine the regulation of silence or pengabain by officials / administrative bodies of the state on requests for state administrative decisions (fictional KTUN). The regulation of the fictitious KTUN currently regulated in Law No. In 1986 concerning the State Administrative Court, Law No. 14 of 2014 concerning Government Administration and Supreme Court Regulation No. 7 of 2018 concerning Procedure Guidelines for Obtaining Decisions Upon Acceptance of Requests to Obtain Decisions and / or Actions by the Agency or Government Officials. The fictitious KTUN arrangements in the three regulations are mutually contradictory, giving rise to confusion in their application. This study attempts toexamine differences in settings, legal consequences and solutions to these differences. This study uses a type of normative research that is prescriptive in nature using a legislative approach and analytical approach. In the case of facing vague legal norms or unclear norms, the judge interprets the Law to find the law. Interpretation by the judge is an explanation that must lead to the implementation that is acceptable to the public regarding legal regulations against concrete events. The method of interpretation is a suggestion or tool to find out the meaning of the law.How to cite item: Ramdani, F. (2018). Keputusan Tata Usaha Negara Fiktif Berdasarkan Hukum Positif Di Indonesia. Jurnal Cakrawala Hukum, 9(2), 135-141. doi:https://doi.org/10.26905/idjch.v9i2.2763